STUDY OF PUBLIC OPEN SPACE AVAILABILITY OF UPNVJT FACULTY IN SOCIAL DEFENSE - Prastyo, Aloysius Yoga Soni Haryo; Ambararum, Dwi Ayu; Afiyah, Nailatul; Elviana, Eva (ADBE, 2023)
Public spaces are an important part of the campus because they serve as areas where activities and interactions among students take place. Spaces that provide opportunities for interaction should meet certain criteria, such as being conducive to such interactions. On the other hand, territories refer to places claimed by individuals or groups to carry out their activities and express their identities. Territories serve as a form of social defense. Based on the explanation above, it is evident that the availability of public spaces in each faculty is crucial, as indicated by their respective territories, which reflect the identities of their users. Therefore, efforts are needed to assess the availability, function, and identity of open public spaces in each faculty at UPN Veteran Jawa Timur. This research utilizes a qualitative research method with a descriptive approach. Field observations are conducted to gather the necessary data. Subsequently, a descriptive analysis is performed to determine the requirements and conditions of public spaces needed by students. Through this process, the availability, function, and identity of open public spaces in each faculty, which contribute to the study of the availability of public spaces within the defense scope, will be obtained.